Bending of wavy spider web honeycomb sandwich structures using PLA - Solak, Alparslan; Temiztas, Birgul Ascioglu; Bolat, Berna (WALTER DE GRUYTER GMBH, 2025)
This study investigates the bending performance of wavy spider web honeycomb sandwich structures produced using polylactic acid (PLA) through 3D printing technology. The primary objective is to enhance mechanical efficiency per unit mass by integrating wave and spider web profiles, a novel approach in the literature. Tensile specimens and sandwich structures were manufactured according to ASTM standards, and their mechanical properties, including stress-strain curves, modulus of elasticity, and Poisson's ratio, were determined through tensile tests. Bending tests on straight, wavy, and spider web designs were conducted to obtain force-deformation curves and post-testing damage images. Finite element models in Ls-Dyna, validated by experimental data, showed that the wavy model achieved the highest specific energy absorption (sEA) while the spider web model exhibited the highest specific peak crushing force (sPCF). The wavy spider web model demonstrated the second-highest values for both metrics, supporting the development of next-generation sandwich structures where specific strength and energy absorption are critical.
Keywords: 3D printing; bending behavior; bioinspired design; honeycomb structures; Ls-Dyna; sandwich structures; Materials Science